1999
DOI: 10.1103/physrevb.60.7238
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen motion inC15-typeZrMo2Hx

Abstract: In order to determine the parameters of H motion in the cubic (C15-type͒ Laves phase ZrMo 2 , we have performed quasielastic neutron scattering measurements and nuclear-magnetic-resonance measurements of the proton spin-lattice relaxation rate on ZrMo 2 H x (0.3рxр1.0) in the temperature range 10-430 K. The diffusive motion of hydrogen in this system can be described in terms of two jump processes: the fast localized H motion within the hexagons formed by interstitial g (Zr 2 Mo 2 ) sites and the slower hoppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
7
22
0
Order By: Relevance
“…This has been confirmed by recent QENS experiments for ZrCr 2 H x [13], ZrMo 2 H x [14], HfMo 2 H x [15] and ZrV 2 H x [16,17]. However, in these systems the difference between the two frequency scales of H motion appears to be smaller than in TaV 2 H x .…”
Section: Systematics Of Two Frequency Scales Of H Jump Motion In Cubisupporting
confidence: 84%
See 3 more Smart Citations
“…This has been confirmed by recent QENS experiments for ZrCr 2 H x [13], ZrMo 2 H x [14], HfMo 2 H x [15] and ZrV 2 H x [16,17]. However, in these systems the difference between the two frequency scales of H motion appears to be smaller than in TaV 2 H x .…”
Section: Systematics Of Two Frequency Scales Of H Jump Motion In Cubisupporting
confidence: 84%
“…Besides TaV 2 H x , two well-resolved R 1 (T ) peaks have been observed only for HfMo 2 H x [18] and Nb(V 1−y Cr y ) 2 H x (D x ) [19]. NMR data for other cubic Laves-phase hydrides including TiCr 1.8 H x [4], ZrCr 2 H x [20], HfV 2 H x and ZrV 2 H x [5,21] and ZrMo 2 H x [14] do not show any additional low-temperature R 1 peak; the localized H motion in these systems contributes only to the low-temperature slope of the single-peak R 1 (T ) dependence. In order to find out why the difference between the two frequency scales of H motion is most pronounced for TaV 2 H x , we may compare the ratios r 2 /r 1 in different Laves-phase hydrides.…”
Section: Systematics Of Two Frequency Scales Of H Jump Motion In Cubimentioning
confidence: 88%
See 2 more Smart Citations
“…While such a hopping was previously observed in non-stoichiometric Laves phase compounds [12][13][14][15], it was surprising to see it in Pr 2 Fe 17 H 5 , where the repulsive interaction between the two H atoms populating a hexagon might be expected to hinder the jumps. We have suggested that the jumps of these two H atoms must be correlated (that is, the simultaneous jumps of two atoms in the same direction must occur) in order to reconcile the dynamics of hydrogen hopping in Pr 2 Fe 17 H 5 with the Switendick criterion of minimal hydrogen separation distance.…”
Section: Introductionmentioning
confidence: 90%